Analisis Dampak Penerapan PSAK 73 (Sewa) terhadap Efisiensi Pajak dan Laba Bersih: Studi Kasus pada PT Mitra Adiperkasa Tbk - Meilani Ely Nur Sya'diah; Moh. Iskak Elly; Dyah Ayu Perwitasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research aims to analyze the implications of the transition in lease accounting standards to PSAK 73 on tax efficiency levels and net income structures within the retail industry, focusing on PT Mitra Adiperkasa Tbk as case studies. Employing a descriptive quantitative method, this research compares financial statement data from the 2017-2024 period to evaluate shifts before and after the regulation's enforcement. The results reveal that the implementation of PSAK 73 successfully improved corporate tax efficiency, characterized by a decrease in the Effective Tax Rate (ETR) below the statutory corporate tax rate. This was achieved by leveraging temporary differences that resulted in the recognition of deferred tax assets, providing a strategic advantage in the form of tax deferral. On the other hand, the application of this standard caused significant pressure on net profit during the initial transition phase due to the front-loading expense pattern derived from right-of-use asset depreciation and lease liability interest.